Penggunaan Media Peta untuk Meningkatkan Hasil Belajar Ilmu Pengetahuan Sosial Kelas V - Tustiyana Windiyani (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
The research was conducted using Classroom Action Research (CAR) collaboratively within two cycles. The aim of the research is to find out the improvement of students’ achievement on social science subject using a map as a learning media to the fifth graders. The subjects of the research were a teacher and fifth grade students at Sekolah Dasar Negeri Puspasari in a district of Bogor. The number of the students was 34 with the composition of 16 girls and 18 boys. The research result shows that the students’ average score at the first cycle was 63 with the percentage of 44% while in the second cycle the average score improved to 76 with the percentage of 97%. There was an improvement of students’ achievement or an improvement of completion as much as 53%. The same result was gained from students observation. There was an increase in students’ participation and activities from 66 at the first cycle to 79 at the second cycle. The research result shows that the use of a map as a learning media is able to improve students’ achievement on social science subject conducted to students of the fifth grade at Sekolah Dasar Negeri Puspasari in a district of Bogor. Besides that, the use of a map in social science class is also able to improve students’ participation and activities in the learning process.